KARAKTER PROGRESIF MATERI MUATAN PERATURAN DAERAH (Perspektif Keberpihakan Penyelenggaran Pelayanan dasar Pemerintah Daerah Terhadap Masyarakat Miskin) - HS Tisnanta (Jurnal Media Hukum, 2012)
Basic service management is the obligation of Local government and one of the constitutional rights of citizen. Basic service is run based on Local Regulation (Perda) which is oriented for the prosperity of society especially for poor society. Based on that condition, it is required a progressive character of perda for guarantying availability, accessibility, and service quality.